Reculturação, reestruturação e reorganização temporal de professores no ambiente digital - Jesus, Dánie Marcelo de (2007)
The sweeping changes taking place in society in the last decades have been requiring new configurations in educational practices. Teachers and students are invited to attend learning environments mediated by computer. Taking this need into account, this study contemplates the distance education context and aims at analyzing reculturing, restructuring and retiming processes (Fullan, 1996) in teacher-students discourse at Teachers Links Programme at PUCSP, intended for state school teachers of English. The main theoretical underpinning for the research is provided by studies of Fullan (1996), Hannay & Ross (1997) about reculturing, restructuring and retiming processes. The study also addresses the concept of social and teaching presence by Garrison & Anderson (2003). The research questions are the following: 1) How do teachers discourses collaborate for teachers-students live deeply possible reculturing, restructuring and retiming processes? 2) What evidence of reculturing, restructuring and retiming processes can be seen, during the process of learning in the teachers-students messages? The research methodology is based on interpretative approach with analyzing discussion forums and interviews with the participants. Results suggest some linguistic data that can characterize processes of reculturing, structuring and retiming processes in the teachers-students discourses